Game-point tactics and training strategy for world-level competitions: what we can learn from the London 2012 Olympic Table Tennis Games - Wu, T. (International Journal of Table Tennis Sciences, 2013)
Similar to a tight basketball or baseball game in late/extra minutes or innings, table tennis competitions often reach a tight late-game situation (score 9-9 and after) of each game in world-level matches. In this study, we first analyzed the matches played in the London 2012 Olympic Games to derive the percentage of games entering the tight late-game situation under different categories of the game margin (4:0, 4:1, 4:2, and 4:3; an indicator of the skill differential between the athletes) and genders. The result reveals the frequency and importance of having game-point tactics and training strategy to prepare for world-level competitions. We then used team China as the study target to describe the preparation logics and the methods employed in their pre-Olympic training camp. Interviews and literature review were both used to collect information about the training content and intensity. At the end, coaching suggestions will be discussed in this study about maneuvers of different score situations to execute the designed services and strokes based on the scouting report to create technical and mental advantages over opponents.